2020
DOI: 10.1136/bmjqs-2019-010742
|View full text |Cite
|
Sign up to set email alerts
|

Standardised approach to measuring goal-based outcomes among older disabled adults: results from a multisite pilot

Abstract: BackgroundOlder adults with complex care needs face trade-offs in determining the right course of treatment. The Centers for Medicare and Medicaid Services identified ‘Care is personalized and aligned with patient’s goals’ as a key meaningful measures category, yet existing quality measures typically assess disease-specific care and may not effectively evaluate what is most important to older adults and family members. Measures based on individualised goals and goal-based outcomes have been proposed as an alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…The patient portal not only allows patients to view sections of their electronic medical record, perform health management tasks (e.g., schedule visits, pay bills, fill prescriptions), access education, and interact with clinicians using secure messaging but may also be used to collect patient‐reported health information that could facilitate patients proactive reporting of goals. Although emerging evidence speaks to the feasibility of deploying goal‐oriented care in practice, 39,46,52 there are practical challenges regarding the specification of goals and their measurement and interpretation. Moving toward goal‐based care will require not only attending to the elicitation and respect of individual goals but collaboration among medical and community‐based organizations, as health care alone cannot facilitate individuals achieving goals in which health is just one component (e.g., as given in Giovannetti et al, 46 “to move to an assisted living facility in the next three months”).…”
Section: Discussion: Opportunities To Further the Field Of Engagement Among Persons With MCCmentioning
confidence: 99%
“…The patient portal not only allows patients to view sections of their electronic medical record, perform health management tasks (e.g., schedule visits, pay bills, fill prescriptions), access education, and interact with clinicians using secure messaging but may also be used to collect patient‐reported health information that could facilitate patients proactive reporting of goals. Although emerging evidence speaks to the feasibility of deploying goal‐oriented care in practice, 39,46,52 there are practical challenges regarding the specification of goals and their measurement and interpretation. Moving toward goal‐based care will require not only attending to the elicitation and respect of individual goals but collaboration among medical and community‐based organizations, as health care alone cannot facilitate individuals achieving goals in which health is just one component (e.g., as given in Giovannetti et al, 46 “to move to an assisted living facility in the next three months”).…”
Section: Discussion: Opportunities To Further the Field Of Engagement Among Persons With MCCmentioning
confidence: 99%
“…More recent approaches that promote goaloriented care and assess individual goal attainment are promising. [41][42][43] On the other hand, studies in the field of multimorbidity have shown contrasting results on quality of life, even if a goaloriented, patient-centred approach was used. 37…”
Section: Limitationsmentioning
confidence: 99%
“…These quality metrics would evaluate the process for collaboratively identifying patient goals and care preferences and the degree to which patient goals are attained. In the current issue of BMJ Quality and Safety, Giovannetti et al 17 describe the results of an innovative study that evaluated the feasibility of two different approaches to developing quality measures of goals-based care. The study assessed the implementation of these measures into diverse clinical settings and the subsequent interpretability and usefulness of the measures based on the data generated from either approach.…”
Section: Measuring Goal Attainment As a Patient-centred Care Quality mentioning
confidence: 99%
“…As Giovannetti and colleagues describe, the key gap in evaluating goals-based care is the presence of measures for setting and documenting goals as well as tracking goal progress and attainment. 17 In routine care, patient goals and care preferences are infrequently and haphazardly written and communicated, often conflicting, and typically focus on end-of-life care or chronic disease biomarkers. [18][19][20][21] To address these gaps, the authors adapted goal attainment scaling, a reliable and valid approach for measuring goal setting and goal attainment in research studies.…”
Section: Measuring Goal Attainment As a Patient-centred Care Quality mentioning
confidence: 99%
See 1 more Smart Citation